2013
DOI: 10.1149/05701.0471ecst
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Metal-Supported SOFC Development and Industrialization at Plansee

Abstract: Benefiting from a strong cooperation with Forschungszentrum Jülich, Karlsruhe Institute of Technology (KIT), and AVL List GmbH respectively, Plansee has been focusing on the development and industrialization of metal-supported SOFC and components for mobile applications. In the scope of some challenging development projects a novel MSC configuration and a first pilot fabrication route could be demonstrated successfully. Currently, the work is ongoing towards a continuous and reliable manufacturing of standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…When the fuel gas is switched to a system-relevant simulated diesel reformate (50% N 2 , 15% H 2 14% CO, 11% H 2 O, 10% CO 2 ) and a temperature of 750 °C cell performances in the range of 200 to 630 mW/cm 2 at 0.7 V were recorded [26], which is sufficient for the application of this type of cell in a mobile APU.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the fuel gas is switched to a system-relevant simulated diesel reformate (50% N 2 , 15% H 2 14% CO, 11% H 2 O, 10% CO 2 ) and a temperature of 750 °C cell performances in the range of 200 to 630 mW/cm 2 at 0.7 V were recorded [26], which is sufficient for the application of this type of cell in a mobile APU.…”
Section: Resultsmentioning
confidence: 99%
“…The setup has been published earlier [26] and will only be discussed briefly. The interconnector frame was made up of dense ITM and accommodates the gas distribution manifolds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to 2010, the German Aerospace Center (DLR) had introduced thermal spray processes for cell fabrication . The original cell was based on NiO + YSZ//YSZ//LSM and generated power density of 150 mW/cm 2 power density at 0.7 V at 800°C.…”
Section: Review Of Technology and Product Developmentmentioning
confidence: 99%
“…Considerable progress both in fundamental and applied aspects in MS-SOFCs has been obtained in recent years. For example, micro combined heat and power (mCHP) unit based on the MS-SOFC has been demonstrated by Ceres Power [2], a plasma sprayed MS-SOFC stack delivered a power of 606 W at 42.4% fuel utilization has been put forward in the Institute of Nuclear Energy Research in Taiwan [3], the potential of MS-SOFC for mobile applications has also been demonstrated in Plansee [4].…”
Section: Introductionmentioning
confidence: 99%